Study of genetic diversity of globulin proteins in soybean (Glycine max (L.) Merr.) genotypes - Gunay H. Zeynalova; Saltanat A. Aghayeva (Acta Biologica Sibirica)
In the study, electrophoretic analysis of globulin storage proteins was performed in 32 samples of local and introduced soybean plants. The goal was the identification, passportization, and study of the genetic diversity of soybean genotypes. In addition, the genetic diversity index (H-) was calculated for zones (ω-, ϒ- β- and α-) according to the frequency of occurrence of patterns in the electropherograms of globulin storage proteins in the seeds of soybean plant samples. 26 spectra and 56 patterns were detected in soybean samples, and polymorphism was observed in most of them. 9 spectra and 20 patterns were observed in the ω-zone, 5 spectra and 8 patterns in the ϒ-zone, 5 spectra and 7 patterns in the β-zone, and 7 spectra and 21 patterns in the α-zone. The genetic diversity index was calculated based on Nei's formula for each of the 4 zones - ω, ϒ, β, and α. According to the calculations, genetic diversity was observed to be higher in the α - zone (H=0.927), slightly lower in the ω- (H=0.796) and ϒ- (H=0.680) zones, and the lowest in the β- zone (H= 0.480). Based on cluster analysis, genotypes were divided into 6 groups and subgroups. Based on the obtained results, electrophoretic analysis of globulin storage proteins was performed for the first time in polyacrylamide gel (A-PAGE) and polymorphism was detected among soybean genotypes.